CRABP2 Promotes the Proliferation of Dermal Papilla Cells via the Wnt/β-Catenin Pathway - Mingliang He; Xiaoyang Lv; Xiukai Cao; Zehu Yuan; Kai Quan; Tesfaye Getachew; Joram M. Mwacharo; Aynalem Haile; Yutao Li; Shanhe Wang; Wei Sun (Animals, 2023)
In our previous study of Hu sheep hair follicles, we found that CRABP2 was highly expressed in DPCs, which suggested that CRABP2 may influence the number of DPCs. In the present study, we aimed to understand the effect of CRABP2 in Hu sheep dermal papilla cells (DPCs). First, we explored the influence of CRABP2 on the ability of Hu sheep DPCs’ proliferation. Based on the results obtained from some experiments, such as CCK-8, EDU, qPCR, and Western blot experiment, we found that the overexpression of CRABP2 facilitated the proliferation of DPCs compared to the negative control group. Then, we also detected the effect of CRABP2 on the Wnt/β-catenin pathway based on the important function of the Wnt/β-catenin pathway in hair follicles. The results showed that CRABP2 could activate the Wnt/β-catenin pathway in DPCs, and it rescues the proliferation of DPCs when the Wnt/β-catenin pathway was inhibited. In summary, our findings indicate that CRABP2 is a vital functional gene in the proliferation of Hu sheep DPCs. Our study will be of great use for revealing the roles of CRABP2 in the hair follicles of Hu sheep.